Numerical simulation of the thermal effects of localized fires - Balsa, Carlos (2018)
The thermal effects of a localized fire bellow a concrete slab with the length of 10 m and the thickness of 30 cm is simulated. The nonlinear equation of heat transfer was solved by finite differences using an implicit scheme. The appropriate mesh size in the direction corresponding to the heat flux resulting from the fire was defined. The temperature results of the two dimensional simulation does not depend on the dimension of the mesh size in the horizontal direction (perpendicular to the heat flux).